PENDAMPINGAN CALON PESERTA ENGLISH SPEECH COMPETITION PORSENI PAC IPNU IPPNU KECAMATAN BUARAN - Ulya, Inayatul; Ida Ayu Panuntun (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
English is an international language which must be mastered by everyone including the members of IPNU and IPPNU. There were many competitions which were held to support English mastery, one of them is English speech competition. This competition motivated the members of IPNU and IPPNU to develop their English mastery. The purpose of this community service was to give accompaniment to the members of IPPNU Simbang Kulon branch so that they were able to write English speech script and they were able to perform it fluently and confidently in the IPNU IPPNU PORSENI Kecamatan Buaran in2023. The participants of this community service were the members of IPPNU Simbang Kulon branch. This community service was done in some steps. They were planning, implementation, evaluation, and report writing. The result of this community service showed that after joining this agenda, the participants could write English speech script based on the topic, using correct grammar and vocabulary. In addition, the participants were able to perform the speech confidently with the gesture, mimic, and eye contact. The participants were able to pronounce the utterance well and delivered the speech fluently. This community service was done successfully. It was proven that the one of the participants became the winner of the English speech competition in the PORSENI.